2011
DOI: 10.1891/0889-8391.25.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Panic-Relevant Cognitive Processes Among Smokers

Abstract: To further understand the frequent co-occurrence of smoking and panic disorder (PD), we examined panic-relevant cognitive processes among heavy smokers, half of whom were in 12-hour withdrawal, and nonsmokers. All participants (N 5 85) underwent a 5-minute carbon dioxide rebreathing challenge. Prior to the challenge, participants completed questionnaires on reasons for smoking, anxiety sensitivity, and suffocation fear. Results are consistent with a model in which smokers with predisposing risk factors (high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Some cross-sectional studies have found that smokers report higher levels of AS than non-smokers (McLeish et al, 2008; Morissette, Brown, Kamholz, & Gulliver, 2006; c.f., Abrams, Schlosser, et al, 2011), which provide indirect evidence that AS may be related to smoking initiation. Given AS-smoking status relations extend to a sample of individuals with anxiety disorders (Morissette et al, 2006), it is possible that AS is not solely a proxy for manifest anxiety psychopathology and rather a transdiagnostic factor explains variance in smoking status among the population of anxiety-disordered individuals.…”
Section: Trandiagnostic Emotional Vulnerabilities and Smokingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cross-sectional studies have found that smokers report higher levels of AS than non-smokers (McLeish et al, 2008; Morissette, Brown, Kamholz, & Gulliver, 2006; c.f., Abrams, Schlosser, et al, 2011), which provide indirect evidence that AS may be related to smoking initiation. Given AS-smoking status relations extend to a sample of individuals with anxiety disorders (Morissette et al, 2006), it is possible that AS is not solely a proxy for manifest anxiety psychopathology and rather a transdiagnostic factor explains variance in smoking status among the population of anxiety-disordered individuals.…”
Section: Trandiagnostic Emotional Vulnerabilities and Smokingmentioning
confidence: 99%
“…AS has frequently been linked to stronger smoking outcome expectancies for negative reinforcement (e.g., beliefs smoking will reduce negative affect) across adult treatment-seeking heavy smokers (> 20 cig/day; Brown, Kahler et al, 2001), college student daily smokers (Zvolensky, Feldner, et al, 2004), and adult daily smokers from the community (Abrams, Schlosser, Leger, Donisch, Widmer, & Minkina, 2011; Gonzalez, Zvolensky, Vujanovic, Leyro, & Marshall, 2008; Gregor, Zvolensky, McLeish, Bernstein, & Morrisette, 2008; Guillot, Pang, & Leventhal, 2014). Similarly, AS is correlated with greater expectations that abstinence will exacerbate negative affect and other undesired outcomes in regular smokers (Abrams, Zvolensky, Dorman, Gonzalez, & Mayer, 2011; Guillot et al, 2014).…”
Section: Trandiagnostic Emotional Vulnerabilities and Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological challenge paradigms have been utilized in experimental psychopathology research to produce physiological sensations associated with anxiety/panic-like symptoms (e.g. chest discomfort, dizziness, sweating, shortness of breath; Abrams et al, 2008a; 2011a, 2011b). In addition, distress intolerance is most frequently conceptualized as a domain-general trait (Trafton and Gifford, 2011), that an individual’s ability to remain in contact with distress is theoretically situationally indiscriminant.…”
Section: Introductionmentioning
confidence: 99%
“…In the sixth article, Abrams et al (in press) examined panic-relevant cognitive processes among heavy smokers and nonsmokers. Participants underwent a 5-minute carbon dioxide rebreathing challenge.…”
mentioning
confidence: 99%